2004
DOI: 10.1189/jlb.1103561
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofcis-resveratrol on inflammatory murine macrophages: antioxidant activity and down-regulation of inflammatory genes

Abstract: This study investigated for the first time the effects of the cis isomer of resveratrol (c-RESV) on the responses of inflammatory murine peritoneal macrophages, namely on the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) during the respiratory burst; on the biosynthesis of other mediators of inflammation such prostaglandins; and on the expression of inflammatory genes such as inducible nitric oxide synthase (NOS)-2 and inducible cyclooxygenase (COX)-2. Treatment with 1-100 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 43 publications
(62 reference statements)
7
116
0
1
Order By: Relevance
“…Similar to curcumin, inhibition of NF-jB activity by resveratrol is considered to be mediated by blocking IKK activity [38]. Resveratrol also suppresses expression of inflammatory enzymes, such as iNOS and COX-2, in macrophages and various cancer cells through the inhibition of NF-jB activity [35,40,61]. In ovarian cancer cells, resveratrol inhibits the expression of both basal level and growth factor-induced hypoxia-inducible factor-1a (HIF-1a) [8,45].…”
Section: Resveratrolmentioning
confidence: 99%
“…Similar to curcumin, inhibition of NF-jB activity by resveratrol is considered to be mediated by blocking IKK activity [38]. Resveratrol also suppresses expression of inflammatory enzymes, such as iNOS and COX-2, in macrophages and various cancer cells through the inhibition of NF-jB activity [35,40,61]. In ovarian cancer cells, resveratrol inhibits the expression of both basal level and growth factor-induced hypoxia-inducible factor-1a (HIF-1a) [8,45].…”
Section: Resveratrolmentioning
confidence: 99%
“…Fura-2 AM was from Molecular Probes (Eugene, OR, USA). cisresveratrol was prepared at the Departamento de Química Orgánica (Universidade de Santiago de Compostela, Spain) following the method previously described (Leiro et al, 2004). All other reagents were of analytical grade.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…The positive effects of resveratrol in biological systems are wide-ranging. It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%